Object-oriented systems in C++ - Pant, Durgesh; Sharma, M. K. (Mahesh Kumar), 1941-; Vaisla, K. S. (Firewall Media, an imprint of Laxmi Publications Pvt. Ltd., 2018)
Object-Oriented Systems in C++ covers the syllabus of UP Technical and Uttaranchal Technical University. Its main objective is to teach how to design and develop a real world system using object-oriented modeling concepts and later how to write a program in C++ and how to make proper use of its features in computer programs. This book starts with a concise introductory text on object-oriented methodologies free from complex definitions in order to facilitate clear-cut understanding of OOAD and use of C++ language to implement it in a very short span of time. All the chapters have been analysed in a tutorial style based explanation of OOAD and C++ concepts through examples with a reference style. The book makes the learning for students very easy.